Design and Construction of a Solar Installation System for a Reading Room at St. Johns Secondary School Ikumba. - Turyashemererwa, Norbet (Kabale University, 2024)
The purpose of this project was to design and construction of a solar installation system for a reading room at ST. Johns secondary school Ikumba. The project was guided by the following objectives: To identify the required components to set up the solar installation system: To build up and install the solar system by using the required components: To evaluate the already set up solar system. This project was based on applied research which aims to solve our problems, save energy, protect our environment, and encourage us not to use fossil fuels but instead be an eco-friendly human. It is radiant heat from the sun that's a natural source of energy using a range of ever-changing and developing technologies such as solar thermal energy, solar architecture, solar heating, molten salt power plants, and artificial photosynthesis. PV cells convert sunlight to direct current (DC) electricity. The battery system acts as a storage of electric power used when sunlight is not available, that's to say, at night. This system is connected to the inverter for converting direct current (DC) into alternating current (AC), (Shaikh, et al, 2017). The project was intended to serve as another source of alternative energy for a reading room. The installation was successful and worked efficiently as intended. However, during the design of the system requirement, the Solar PV Energy System was implemented. A portion of the energy requirement for a school reading room has been supplied with the electricity generated from solar power. It reduces the dependence on one single source and has increased the reliability. Apparently, we can improve the efficiency of the system with an individual interest mode of generation. Solar panel systems are cost-effective, pollution-free, and maintenance-free.